Ultrasonic and hypersonic investigations of structural relaxation in aqueous solutions of Hexamethylphosphortriamide - Piotr MIECZNIK (Archives of Acoustics)
Measurements of the absorption coefficient of ultrasonic waves in the frequency range 10-100 MHz and of the propagation velocity of ultra- and hypersonic waves in aqueous solutions of Hexamethylphosphortriamide (HMPT) were carried out. In addition the density of the solutions and the coefficient of shear viscosity was measured. On the basis of the quantities measured, the coefficient of bulk viscosity, relaxation parameters of the process observed and, on the basis of the theory of compressibility relaxation, change in free energy and volume between two structural states were measured. The analysis of the results of measurements of the absorption coefficient of ultrasonic waves, depending on the frequency, temperature, and composition of solutions, shows the presence in aqueous solutions of HMPT of a relaxation process related to the formation and disintegration of clathrate structures with the composition HMPT · 17 H2O. On the basis of compressibility relaxation theory, it was shown that the process of structural relaxation is related to a change in volume ΔV and in free energy ΔF between two structural states.